Perianal Fistula Due to Tuberculosis Infection: A Case Report - Sinaga, Bintang Yinke Magdalena; Siagian, Novi Andriani; Siagian, Parluhutan; Muhar, Adi Muradi (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Introduction: Approximately 5% of all cases of tuberculosis are extrapulmonary. A rare extrapulmonary variant of the disease is known as perianal tuberculosis, which accounts for 0.001% of all extrapulmonary tuberculosis cases. Case Report: A 28-year-old male presented with intermittent chronic anal pain and purulent discharge from the anal for 6 months, without respiratory complaints. Chest X-Ray examination shows minimal infiltrate on the right lung apex and broncho vascular pattern partially covered with infiltrate. Fistulotomy has been done three times in this patient within 6 months. Colonoscopy examination shows recti polyp, and the histopathology result from biopsy specimen taken from the last fistulotomy is tuberculosis-specific chronic inflammatory process. The Human Immunodeficiency Virus test is negative. This patient has been treated with anti-tuberculosis treatment for 7 months and 2 months after consuming it the wound on the perianal is healing and the patient’s weight is gaining 10 kgs within 7 months. Conclusion: The diagnosis of perianal tuberculosis is challenging, especially in the absence of pulmonary focus. Tuberculosis should be considered in the differential diagnosis of perianal ulcers and fistulas, mainly in non-healing and recurrent anal lesions, especially in regions where tuberculosis is endemic. Management with anti-tuberculosis treatment can provide complete recovery.